Chinese students’ filial piety beliefs and procrastination in mathematics learning: The mediating role of academic emotions - Guo, Meng; Cao, Yiming; Hu, Xiang (Frontiers in Psychology, 2023)
This research examined the relation between Chinese students’ filial piety beliefs and mathematics procrastination and the mediating role of academic emotions in the relations. Data analysis on 1476 primary school students in China with structural equation modelling revealed that students’ reciprocal and authoritarian filial piety beliefs were positively related to academic enjoyment and anxiety, respectively. Students’ procrastination in mathematics learning was positively predicted by anxiety and authoritarian filial piety beliefs and had negative relationships with enjoyment and reciprocal filial piety beliefs. Bootstrap analysis results confirmed anxiety’s mediating role in the relationship between authoritarian filial piety beliefs and procrastination and the reciprocal filial piety beliefs’ negative indirect relationship with procrastination via enjoyment. The results are explained from a socio-cultural perspective. Theoretical contributions and practical implications are discussed.